Pronunciation of Bachelor of Arts Students at Faculty of Humanities, Mahachulalongkornrajavidyalaya University, Khon Kaen Campus, Thailand - Baotong, Kristina; Kanokkamalade , Veerakarrn; Pintrymool, Narongchai (วารสารจิตวิทยาพุทธศาสตร์ประยุกต์เพื่อสังคม, 2021)
The purposes of this study were 1) to study the problems of the English pronunciation of Bachelor of Arts students at Faculty of Humanities, Mahachula longkornrajavidyalaya University, Khon Kaen Campus, Thailand 2) to propose the solution of the English pronunciation skills of Bachelor of Arts students at Faculty of Humanities, Mahachulalongkornrajavidyalaya University, Khon Kaen Campus, Thailand. The study was mixed researches between a quantitative method and qualitative method. A questionnaire was used for collecting quantitative data from 40 students who are studying In Bachelor of Arts at Faculty of Humanities, Mahachulalongkornrajavidyalaya University, Khon Kaen Campus. And in-depth interview was used for collecting qualitative data from 15 key informants, including 10 students who are studying and 5 teachers who are teaching at Faculty of Humanities, Mahachulalongkornrajavidyalaya University, Khon Kaen Campus. The statistics used for quantitative data analysis were frequency, percentage, mean, and standard deviation and a content analysis was used for analyzing qualitative data. The results of the research were as follows: The study of “The English pronunciation of Bachelor of Arts Students at Faculty of Humanities, Mahachulalongkornrajavidyalaya University, Khon Kaen Campus. According to the research methodology, there were mixed research between quantitative research and qualitative research. The quantitative data that the researcher collected from 4 parts of questionnaires with 40 students as follows: 1) The overall level of the students’ attitudes to the English pronunciation was high level with mean 4.48. 2) The overall level of the students’ methods of learning the English pronunciation was the high level with mean 4.14. 3) Therefore, the overall level of the students’ difficulties in learning English pronunciation was the high level with mean 3.74. 4) the overall level of the teachers’ roles of developing the English pronunciation was the high level with mean 4.47. And qualitative data were as follows: as the results was found that the students lacked the opportunity, they did not have space and time to practice themselves, just only in the class of in the university. Because of cultural aspect, they always spoke Thai and Isan at home, they had also lack of motivation, they felt shy to speak. When they were practicing, someone laughed at them. They did not have motivation to practice the English pronunciation. And the result of the way to solve the problem was firstly, asking them to read more English books, practicing to read aloud and correcting their pronunciation. Since the students felt shy to speaks, they had to motivate themselves to practice and speak in the public space and encouraged them to listen to English songs, watching the VDO of native speakers on YouTube, to see how they pronounce, how they produce the words. And then they try to pronounce or practice following the native speakers.